"The Burning Fire of Love, the Nucleus of Reconciliation": Dietrich Bonhoeffer and the Theme of the 11th Assembly of the World Council of Churches. Issue 2 (13th June 2021) - Clements, Keith
Abstract: In 2022, the 11th Assembly of the World Council of Churches will gather in Karlsruhe, Germany, around the theme "Christ's love moves the world to reconciliation and unity." Since its 20th‐century beginnings, the modern ecumenical movement has been closely bound up with developments in Germany, not least during the period of the Third Reich. Its early protagonists included the Protestant theologian Dietrich Bonhoeffer, who was executed in 1945 for his resistance to National Socialism. This article considers the theme of the forthcoming WCC assembly in 2022, "Christ's love moves the world to reconciliation and unity, " from the perspective of the life and writings of Bonhoeffer, for whom speaking of reconciliation and unity raises the question of the relationship of the church as the body of Christ to the whole of humanity and the whole created order embraced by the reconciling love of God in Christ.